Causal Relationship Among Professional Learning Communities and Teaching Self-Efficacy: A Study Among Teaching Staff in Betong, Sarawak - Ying-Leh Ling; Wei-Shang Wang (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2023)
The Professional Learning Community (PLC) serves as a platform where teaching staff collaboratively create learning opportunities to enhance the overall teaching and learning process in classrooms. In the developing world, educators play a crucial role in driving development through education, making PLCs particularly relevant. By participating in PLCs, teachers can boost their self-esteem, gain insights into effective teaching methods, and acquire valuable knowledge to improve student performance. Additionally, this program fosters a cooperative culture among teachers and supports continuous lifelong learning. PLC's benefits have garnered international recognition, including in Malaysia. To delve into the perceptions of teachers in rural primary schools in Betong, Sarawak, regarding the implementation of PLC, this study was conducted. Furthermore, the research aimed to assess the level of teacher self-efficacy and explore the potential relationship between the implementation of PLC and teacher self-efficacy. Employing quantitative methods, the study collected responses from 150 rural primary school teachers based on five selected national primary schools, using a well-structured questionnaire to gather data. The study's findings indicate that a significant number of teaching staff possess knowledge about the implementation of PLC and express optimism about the way it is conducted in their respective schools. Teachers are reported to be highly effective in managing classrooms, engaging students during the teaching and learning process, and employing quality teaching strategies. Moreover, the study reveals a noteworthy relationship between various dimensions of PLC and teacher self-efficacy. The implications of these findings are both theoretical and practical. For instance, it underscores the importance of fostering PLCs in schools to empower teachers, improve their confidence in their abilities, and promote a conducive learning environment. By nurturing a culture of collaborative learning and professional development, educational institutions can elevate teaching standards, ultimately leading to enhanced student outcomes. The study's insights can guide policymakers and school administrators in designing and implementing effective PLC initiatives, ensuring they have a positive impact on both teachers and students